Pembelajaran Matematika Berbasis Problem Based Learning Terintegrasi Scratch untuk Mengembangkan Computational Thinking Siswa SD - Nita Dwi Ariyanti; Riyadi Riyadi; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2026)
Mathematics learning in elementary school requires systematic and logical thinking skills; however, students’ computational thinking skills remain relatively low due to the limited use of interactive learning models. This study aims to examine the effect of Scratch-assisted Problem-Based Learning on improving students’ computational thinking skills. A quantitative approach was used, employing a quasi-experimental method and a nonequivalent control group design. The study sample consisted of 104 students, comprising 58 students in the experimental group and 46 students in the control group. Data were collected using computational thinking tests based on word problems involving the LCM and GCF, administered as pretests and posttests. Data analysis included tests for normality, homogeneity, balance, and hypothesis testing using the Independent Samples t-test. The results showed that the mean posttest score for the experimental group (85.482) was higher than that of the control group (62.478), with a significance level of 0.000 < 0.05, indicating a significant difference. These findings prove that Scratch-assisted Problem-Based Learning is effective in improving students’ computational thinking skills. Therefore, Scratch-assisted Problem-Based Learning can serve as an alternative innovative learning strategy in elementary school mathematics education.